Last man off : a true story of disaster and survival on the Antarctic seas - Lewis, Matt, 1974- (Plume, 2015)
"'A sinister version of The Perfect Storm. Thrilling'--Sunday Times (UK). There's nothing that armchair adventure lovers relish more than a gripping true story of disaster and heroism, and Last Man Off delivers all that against a breathtaking backdrop of icebergs and killer whales. On June 6, 1998, twenty-three-year-old Matt Lewis had just started his dream job as a scientific observer aboard a deep-sea fishing boat in the waters off Antarctica. As the crew haul in the line for the day, a storm begins to brew. When the captain vanishes and they are forced to abandon ship, Lewis leads the escape onto three life rafts, where the battle for survival begins"--